The role of urban‐based agriculture on food security: Kenyan case studies. (May 2017) - Omondi, Samuel Onyango; Oluoch‐Kosura, Willis; Jirström, Magnus
Abstract: Kenya is rapidly urbanising. In the growing cities and towns, there is an increasing need for food supplies, creating demand for agricultural products. High unemployment rates, urban poverty, and food and nutrition insecurity force some urban dwellers to partly adopt livelihood strategies based on urban agriculture. Presently in Kenya, urban and peri‐urban agriculture plays an important role in urban food system, because it enhances livelihood strategies for urban households, not least the poor. Using a sample of 2, 009 households, this study characterised urban farming and urban‐based rural farming in medium‐sized towns of Thika and Kisumu, Kenya. It further assessed food security levels of urban households engaged in farming and households that do not farm. Results demonstrate that more than half of the households produced part of their food, either in urban or rural areas. About 37 per cent and 25 per cent of the respondents produced food in rural and urban areas, respectively. Generally, more of the households engaged in both urban farming and urban‐based rural agriculture are more food secure compared with the non‐farming households. Urban farming has a potential of improving household food security and provision of fungible income; hence, the practice should be included in the urban food policies.